Occurrence, Source Apportionment, and Risk Assessment of Antibiotics in the Zhuozhang River, China: A Specific Investigation in Water-Scarce and Human Activity-Intensive Regions - Juping Yan; Xiayang Wu; Ke Dong; Zhiyuan Zhang; Xuejun Sun; Shaopeng Gao; Jinxian Liu; Baofeng Chai (Toxics, 2025)
Antibiotic contamination and its environmental impact in water-scarce and human activity-intensive regions have been poorly researched, particularly in the Zhuozhang River, China. Thus, this study investigated the occurrence, sources, and ecological risks of 27 different antibiotics in the Zhuozhang River, based on water samples collected from representative locations including major reservoirs, upstream of the river, the main river channel, and a wastewater treatment plant (WWTP). Results showed widespread contamination by quinolones, with concentrations ranged from 41.7 to 184.3 ng/L. Quinolones—particularly ofloxacin and cinoxacin—were identified as posing moderate ecological risks, with heightened concerns in the main river channel and wastewater treatment plant areas. Source apportionment using the positive matrix factorization model identified livestock farming as the dominant contributor to antibiotic pollution, accounting for 22.9% of the total antibiotic load in the river. These findings underscore the urgency of enhancing monitoring and management strategies to mitigate antibiotic contamination, especially in high-risk areas such as wastewater treatment plants and main river sections.